2013
DOI: 10.1002/ase.1352
|View full text |Cite
|
Sign up to set email alerts
|

Histological knowledge as a predictor of medical students' performance in diagnostic pathology

Abstract: Over the years, the role and extent of the basic sciences in medical curricula have been challenged by research on clinical expertise, clinical teachers, and medical students, as well as by the development and diversification of the medical curricula themselves. The aim of this study was to examine how prior knowledge of basic histology and histopathology among students predicts early learning of diagnostic pathology. Participants (N=118, representing 91% of the full student cohort) were medical students at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…where knowledge of tissues, obtaining samples for biopsy, and interpreting microscopic specimens are critical to job performance. Nivala et al (2013) found that students' prior histological knowledge is a predictor of medical student performance in diagnostic pathology, confirming the value of having a strong background in the basic medical sciences.…”
Section: Introductionmentioning
confidence: 55%
“…where knowledge of tissues, obtaining samples for biopsy, and interpreting microscopic specimens are critical to job performance. Nivala et al (2013) found that students' prior histological knowledge is a predictor of medical student performance in diagnostic pathology, confirming the value of having a strong background in the basic medical sciences.…”
Section: Introductionmentioning
confidence: 55%
“…For example, it has been suggested that biomedical understanding acts as a mediator in such reasoning, since students with misconceptions in biomedical knowledge also appear to perform poorly in clinical reasoning, while those with excellent clinical reasoning skills remarkably improve their biomedical knowledge during preclinical studies (Ahopelto et al, ). Further, Nivala et al () confirmed the long‐term value of basic science studies in the preclinical phase by showing that performance in diagnostic pathology was predicted by students' prior knowledge of histology, even after a relatively long time delay between measurements.…”
Section: Introductionmentioning
confidence: 94%
“…There appears to be a consensus regarding the value of biomedical knowledge as a foundation for clinical knowledge, but the precise role of biomedical knowledge in clinical reasoning remains a subject of debate (Kaufman et al, ). Recent studies have indicated that the biomedical basic science knowledge taught at the beginning of medical studies plays a central role in students' clinical reasoning (Ahopelto et al, ; Nivala et al, ). For example, it has been suggested that biomedical understanding acts as a mediator in such reasoning, since students with misconceptions in biomedical knowledge also appear to perform poorly in clinical reasoning, while those with excellent clinical reasoning skills remarkably improve their biomedical knowledge during preclinical studies (Ahopelto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Basic knowledge of histology and histopathology predict early learning of diagnostic pathology. 2 Classical clinical presentations along with characteristic radiological and histopathological patterns are suggestive of a particular tumour or group of tumours; thereby aid in providing a correct histopathological diagnosis. 3 Collective clinical, radiological and histopathological analysis helps in formulating a list of differential diagnosis, and reaching a final diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Both histology and diagnostic pathology rely heavily on microscopic images. 2 Various characteristic patterns have a peculiar picture which resembles with things present in our surrounding environment. These patterns can hence be easily memorised, correlated to reach a proper diagnosis and deliver appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%